Production of indigenous alcoholic beverages in a rural village of Tanzania. Issue 2 (20th February 2014) - Kubo, Ryosuke
<x xml:space="preserve">Abstract</x> In this study, the production techniques of indigenous alcoholic beverages in a rural village in Tanzania were investigated. In the village, three different kinds of alcoholic beverages were produced: a maize turbid beer (komoni), a straw beer (kimpumu) and a hybrid straw beer (kiambule). In the course of the production of these three alcoholic beverages, two different kinds of porridge, a fermented porridge (nyambo) as a source of yeasts and a sweet porridge (kikonde) as a source of saccharides, were produced. These porridges were mixed at the end of the production process. The pH value of fermented porridge was kept below 4 during its preparation. This was effective in preventing contamination of the porridge by harmful bacteria and in stabilizing the growth of the yeasts. Sweet porridge was heated in the range of 50–70 °C and this enhanced the saccharification of the starch in the raw materials. The starting materials of these alcoholic beverages were finger millet and maize. Germinated finger millet, which has a high amylase activity compared with other cereals, was used as an amylase source in each of the alcoholic beverage production processes. Various techniques to enhance and stabilize the quality of the indigenous alcoholic beverages are described. Copyright © 2014 The Institute of Brewing & Distilling